Modeling method for refraction error compensation in ground object detection - Daochun Yu; Zhen Chen (PLoS ONE, 2026)
The refraction error compensation model for ground object detection is established. Firstly, based on a 100-meter interval, the area between the aircraft and the ground objects is stratified, and the Hopfield model of the atmospheric refractive index is combined with the e-index model to achieve an accurate simulation of the atmospheric refractive index profile. Then, based on the information such as the line-of-sight direction, flight altitude, and observation wavelength of the ground object observation target by the aircraft, combined with Snell’s law, the distance from the projection of the aircraft on the Earth’s surface to the true position of the ground object is given, and the true elevation angle is derived. Finally, by calculating the difference between the apparent elevation angle and the true elevation angle of the aircraft, the elevation angle error model of the aircraft is established to correct the elevation angle error of the aircraft caused by atmospheric refraction and is applied to the precise identification and positioning of the observed target.